METAL 2020 Conference Proeedings 2020
DOI: 10.37904/metal.2020.3447
|View full text |Cite
|
Sign up to set email alerts
|

DATA PROCESSING OF MEASURED SURFACE TEMPERATURES OF CONTINUOUSLY CAST BILLETS and blooms TO VERIFY THE NUMERICAL SOLIDIFICATION MODEL

Abstract: Numerical models of solidification and cooling of continuously cast billets or blooms are used both in research and in operational conditions to predict solid shell thickness, metallurgical length, solidification rate etc. The numerical model must be verified according to real values of quantities. Although several different quantities can be used to verify the model, most often the models are verified by comparing the calculated and measured surface temperatures of the strand in the secondary and tertiary coo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…where L is the distance from the meniscus (m), and w is the casting speed (m•min −1 ). However, many experimental measurements have already shown that the growth of the shell does not proceed exactly according to the parabolic law [38]. In the case of continuous casting, which is a much more complicated process dependent on many factors, the shell thickness at a greater depth below the meniscus can be described by empirical regression formulas in the form of the power function of time…”
Section: Modelling Methods Of the Thickness Of The Solid Shellmentioning
confidence: 99%
See 1 more Smart Citation
“…where L is the distance from the meniscus (m), and w is the casting speed (m•min −1 ). However, many experimental measurements have already shown that the growth of the shell does not proceed exactly according to the parabolic law [38]. In the case of continuous casting, which is a much more complicated process dependent on many factors, the shell thickness at a greater depth below the meniscus can be described by empirical regression formulas in the form of the power function of time…”
Section: Modelling Methods Of the Thickness Of The Solid Shellmentioning
confidence: 99%
“…The kinetics of the temperature field of the mould wall generally carries the greatest amount of information about the complex process of solidification. The measured temperature field is evaluated quantitatively in terms of the magnitude of temperatures, qualitatively with regard to the symmetry of cooling, and further from the point of view of its dynamics, i.e., changes in the symmetry of heat removal over time and space and temperature fluctuations [38]. Large temperature fluctuations can indicate an uneven thickness of the shell, an uneven layer of casting powder or imperfect lubrication.…”
Section: Modelling Methods Of the Thickness Of The Solid Shellmentioning
confidence: 99%
“…It is vital for quality stability as most defects may occur during the unsteady process. There heat transfer model generally serves as a software sensor for basic feedback of solidification status, including temperature field and solidified shell thickness, while at present the corresponding hardware measurements [17][18][19][20] are still insufficient, unstable and not accurate enough due to the harsh environment with super high temperature and full of steam. In this case, the real-time model is the only available way for online application at present, and the real-time requirements include both accuracy (being real) and efficiency (being timely).…”
Section: Introductionmentioning
confidence: 99%